A case of Klebsiella pneumoniae spondylitis and bacteremia potentially due to inflammation around a fecalith. Issue 6 (June 2019) - Inagaki, Ayane; Moriyama, Yuki; Morioka, Shinichiro; Wakimoto, Yuji; Shida, Yoshitaka; Ohmagari, Norio
Abstract: We herein report a case of Klebsiella pneumoniae ( K. pneumoniae ) spondylitis and bacteremia in a 90-year-old man with diabetes mellitus who had undergone sigmoidectomy and had a fecalith. Two months prior to admission, he had received antimicrobial treatment for 2 weeks for K. pneumoniae bacteremia whose entry was unclear and he was readmitted to our hospital owing to fever and stomachache. K. pneumoniae was isolated from two sets of blood cultures, and computed tomography and magnetic resonance imaging revealed inflammation and destruction of the 8th and 9th thoracic vertebra. The diagnosis was spondylodiscitis secondary to K. pneumoniae bacteremia. Although the entry point for K. pneumoniae was unclear, we suggest that inflammation of the mucosa around the fecalith might have caused the Enterobacteriaceae bacteremia.